(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In today’s globalized world, education serves as a cornerstone for the development of individuals and societies alike. The Pearls International Assessment Program (PIAP) system stands as a significant benchmark for evaluating student performance worldwide. However, the preparation of primary students for this rigorous assessment system presents several challenges. This article explores the issues surrounding the enhancement of preparatory processes for primary students within the PIAP system. Through a comprehensive review of literature and educational practices, it offers insights into strategies aimed at optimizing student readiness and performance in the PIAP system.